Pengetahuan, Sikap, dan Perilaku Social Distancing Sebagai Upaya Pencegahan COVID-19 Pada Dewasa Muda di Kota Pekanbaru - Tyagita Widya Sari; Sindy Mutiara Irawati; Yurissa Mizar Anggraini (LPPM Universitas Muhammadiyah Riau, 2022)
COVID-19 is a disease that has never been previously identified in humans. This case is increasing day by day in all corners of the world, including in Indonesia. Riau Province has reported 120 confirmed cases of COVID-19 and Pekanbaru City is the area with the most COVID-19 cases from 12 districts/cities. The World Health Organization (WHO) issued a decision so that people can practice social distancing which is very helpful in breaking the chain of COVID-19 transmission. However, some people in Indonesia still consider social distancing to be just an ordinary recommendation, resulting in the implementation of social distancing not being completely evenly distributed. The purpose of this study were to determine the relationship between knowledge and attitudes towards social distancing and the relationship between attitudes towards social distancing and social distancing behavior as an effort to prevent COVID-19 in young adults in Pekanbaru City in 2020. This study used an analytical observational study design with a cross sectional design. This research was conducted on a young adult population in Pekanbaru City in August 2020. The sampling technique used was cluster sampling with a sample of 120 respondents. Data retrieval on respondents was done by online method. Data analysis was carried out by means of the Spearman correlation test to obtain the p-value and correlation coefficient. The results of the Spearman's rho correlation analysis show that there is a significant relationship between knowledge and attitudes towards social distancing (p-value = 0.000) with a correlation coefficient of 0.899. In addition, there is a significant relationship between attitudes towards social distancing and social distancing behavior (p-value = 0.000) with a correlation coefficient value of 0.880. The conclusion of this study are that there is a significant relationship with a very strong correlation strength and a positive direction of correlation between knowledge and attitudes towards social distancing and there is a significant relationship between attitudes towards social distancing and social distancing behavior as an effort to prevent COVID-19 in young adults in Pekanbaru City in 2020.